Making an Integrated Border: Challenges for Immigration Institutions in North Sulawesi - Bataha, Katerina; K. Monintja, Donald; K. Malensang, Romel; P. Barakati, Dijey (International Journal of Science, Technology & Management, 2023)
Border areas are the country's frontline in the face of outside security threats. Thus, strengthening capacity in managing borders must be taken seriously. This research uses a qualitative method, which is a study that aims to explain the challenges faced by immigration institutions in the Province of North Sulawesi related to the integration of border management and what strategies can be offered to overcome various obstacles or challenges that arise in efforts to integrate border management in North Sulawesi. The analysis of the problems in this study will be based on eight parameters of an integrated border management system, namely: (1) Legal and Regulatory Framework, (2) Organization and Management, (3) Procedures, (4) Human resources and training, (5) Communication, (6) Information Technology (7) Infrastructure and (8) Budget. This study took a locus in the Province of North Sulawesi, which has a maritime border with the Philippines, using qualitative methods to explain the integration of border management involving immigration institutions in North Sulawesi.